Communities of faith as texts in the process of biblical interpretation - Jonker, L. (Verbum et ecclesia, 1999)
In this article the author illustrates that the relationship between the Bible and the Church could also be described from the post-modern perspective of intertextuality. He argues that communities of faith are texts in an all-encompassing network of textuality. However, these texts, as all other texts, are involved in clusters of related texts that show an affinity with one another. Within these clusters the related texts become more prominent and significant than texts "further away" in the network of textuality. He uses this view to argue that the Church, along with the Synagogue, has a special responsibility in the process of interpretation of the written biblical texts. He also argues that all the approaches that biblical scholars have utilized through the ages, when viewed as different perspectives on the network of textuality, could assist in our reading of communities of faith as texts.